Biological aspects of Chrysoperla externa (Hagen) preying on Oligonychus ilicis (McGregor) and Planococcus citri (Risso) - Neto, Marçal Pedro; Carvalho, César Freire; Reis, Paulo Rebelles; Santa-Cecília, Lenira Viana Costa; Souza, Brígida; Alcantra, Eliana; Silva, Rogério Antônio (Coffee Science - ISSN 1984-3909, 2008)
The red mite Oligonychus ilicis (McGregor, 1917) and the mealybug Planococcus citri (Risso, 1813) are considered important pests of the coffee plant (Coffea arabica L.), causing yield losses. The predator Chrysoperla externa (Hagen, 1861) is associated with those pests. The objective of this work was to evaluate the development of the immature and adult phases of the predator fed, in the immature phase, on those coffee plant pests and their effects on both fecundity and survival rate of larvae, pupae and eggs in laboratory. The bioassays were carried out in the laboratory of the EcoCentro/CTSM-EPAMIG, Lavras, MG, at 25 ± 1ºC, 70 ± 10% of relative humidity and 12 hours´ photophase. The experimental design was completely randomized with 10 treatments representing the possible combinations of the diets: Anagasta kuehniella (Zeller, 1879) eggs as the standard food, mites and mealybugs, with 30 replicates. The preys were supplied either singly or associated between each other in each instar or alternated in the instars with eggs of A. kuehniella. Significant alterations occurred in weight, larval and pupal survival, when the larvae were fed with only one prey type or with the combination of mites plus mealybugs, compared to eggs of A. kuehniella. It was demonstrated that O. ilicis e P. citri singly supplied to larvae of C. externa, is not the food adequate for the development of larvae. Only the red mite as a food caused 100% of death of the lacewing’s larvae in the second instar.